Pre-adolescence DNA methylation is associated with lung function trajectories from pre-adolescence to adulthood - Sunny, Shadia Khan (Clin Epigenetics, 2021)
BACKGROUND: The pattern of lung function development from pre-adolescence to adulthood plays a significant role in the pathogenesis of respiratory diseases. Inconsistent findings in genetic studies on lung function trajectories, the importance of DNA methylation (DNA-M), and the critical role of adolescence in lung function development motivated the present study of pre-adolescent DNA-M with lung function trajectories. This study investigated epigenome-wide associations of DNA-M at cytosine-phosphate-guanine dinucleotide sites (CpGs) at childhood with lung function trajectories from childhood to young adulthood. METHODS: DNA-M was measured in peripheral blood at age 10 years in the Isle of Wight (IOW) birth cohort. Spirometry was conducted at ages 10, 18, and 26 years. A training/testing-based method was used to screen CpGs. Multivariable logistic regressions were applied to assess the association of DNA-M with lung function trajectories from pre-adolescence to adulthood. To detect differentially methylated regions (DMRs) among CpGs, DMR enrichment analysis was conducted. Findings were further tested in the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort. Pathway analyses were performed on the mapped genes of the identified CpGs and DMRs. Biological relevance of the identified CpGs was assessed with gene expression. All analyses were stratified by sex. RESULTS: High and low trajectories of FVC, FEV(1), and FEV(1)/FVC in each sex were identified. At P(Bonferroni) < 0.05, DNA-M at 96 distinct CpGs (41 in males) showed associations with FVC, FEV(1), and FEV(1)/FVC trajectories in IOW cohort. These 95 CpGs (cg24000797 was disqualified) were further tested in ALSPAC; 44 CpGs (19 in males) of these 95 showed the same directions of association as in the IOW cohort; and three CpGs (two in males) were replicated. DNA-M at two and four CpGs showed significant associations with the corresponding gene expression in males and females, respectively. At P(FDR) < 0.05, 23 and 10 DMRs were identified in males and females, respectively. Pathways were identified; some of those were linked to lung function and chronic obstructive lung diseases. CONCLUSION: The identified CpGs at pre-adolescence have the potential to serve as candidate markers for lung function trajectory prediction and chronic lung diseases.